2021
DOI: 10.3390/life11010041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gabapentin in a Neuropathic Pain Model in Mice Overexpressing Human Wild-Type or Human Mutated Torsin A

Abstract: Background: DYT1 dystonia is the most common form of early-onset inherited dystonia, which is caused by mutation of torsin A (TA) belonging to the “ATPases associated with a variety of cellular activities” (AAA + ATPase). Dystonia is often accompanied by pain, and neuropathic pain can be associated to peripherally induced movement disorder and dystonia. However, no evidence exists on the effect of gabapentin in mice subjected to neuropathic pain model overexpressing human normal or mutated TA. Methods: Mice su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 57 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…However, a trend toward an increased hyperalgesia is present in hWT and hMT mice compared to NT mice, but it does not reach statistical significance. Previous results from our research group have demonstrated that there are no significant differences in baseline mechanical sensitivity among the three strains [ 35 ]. Moreover, the transgenic mice have shown prolonged mechanical allodynia after SNL, suggestive of delayed recovery [ 35 ].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, a trend toward an increased hyperalgesia is present in hWT and hMT mice compared to NT mice, but it does not reach statistical significance. Previous results from our research group have demonstrated that there are no significant differences in baseline mechanical sensitivity among the three strains [ 35 ]. Moreover, the transgenic mice have shown prolonged mechanical allodynia after SNL, suggestive of delayed recovery [ 35 ].…”
Section: Discussionmentioning
confidence: 86%
“…Previous results from our research group have demonstrated that there are no significant differences in baseline mechanical sensitivity among the three strains [ 35 ]. Moreover, the transgenic mice have shown prolonged mechanical allodynia after SNL, suggestive of delayed recovery [ 35 ]. Nevertheless, the effect of the human gene on pain processing cannot be excluded [ 35 ].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations